Copy number variation and expression of exportin-4 associates with severity of fibrosis in metabolic associated fatty liver disease - Mayada Metwally; Ali Bayoumi; Anis Khan; Leon A. Adams; Rocio Aller; Carmelo García-Monzón; María Teresa Arias-Loste; Elisabetta Bugianesi; Luca Miele; Alisi Anna; Olivier Latchoumanin; Shuanglin Han; et al. (EBioMedicine, 2021)
Background: Liver fibrosis risk is a heritable trait, the outcome of which is the net deposition of extracellular matrix by hepatic stellate cell-derived myofibroblasts. Whereas nucleotide sequence variations have been extensively studied in liver fibrosis, the role of copy number variations (CNV) in which genes exist in abnormal numbers of copies (mostly due to duplication or deletion) has had limited exploration. Methods: The impact of the XPO4 CNV on histological liver damage was examined in a cohort comprised 646 Caucasian patients with biopsy-proven MAFLD and 170 healthy controls. XPO4 expression was modulated and function was examined in human and animal models. Findings: Here we demonstrate in a cohort of 816 subjects, 646 with biopsy-proven metabolic associated liver disease (MAFLD) and 170 controls, that duplication in the exportin 4 (XPO4) CNV is associated with the severity of liver fibrosis. Functionally, this occurs via reduced expression of hepatic XPO4 that maintains sustained activation of SMAD3/SMAD4 and promotes TGF-β1-mediated HSC activation and fibrosis. This effect was mediated through termination of nuclear SMAD3 signalling. XPO4 demonstrated preferential binding to SMAD3 compared to other SMADs and led to reduced SMAD3-mediated responses as shown by attenuation of TGFβ1 induced SMAD transcriptional activity, reductions in the recruitment of SMAD3 to target gene promoters following TGF-β1, as well as attenuation of SMAD3 phosphorylation and disturbed SMAD3/SMAD4 complex formation. Interpretation: We conclude that a CNV in XPO4 is a critical mediator of fibrosis severity and can be exploited as a therapeutic target for liver fibrosis. Funding: ME and JG are supported by the Robert W. Storr Bequest to the Sydney Medical Foundation, University of Sydney; a National Health and Medical Research Council of Australia (NHMRC) Program Grant (APP1053206) and Project and ideas grants (APP2001692, APP1107178 and APP1108422). AB is supported by an Australian Government Research Training Program (RTP) scholarship. EB is supported by Horizon 2020 under grant 634413 for the project EPoS.